Methods to evaluate the impact of SARS-CoV-2 nucleocapsid mutations on antigen detection by rapid diagnostic tests - Bryan C Tieman; Stephen Kovacs; Mary A Rodgers; Aurash Mohaimani; Svetoslava Gregory; David Christensen; Jeffrey A Moore; Lici Schurig-Briccio; James Hartnett; Alak Kar; Aaron Leeman; Angel Palmer; et al. (BioTechniques, 2022)
Mutations in the nucleocapsid of SARS-CoV-2 may interfere with antigen detection by diagnostic tests. We used several methods to evaluate the effect of various SARS-CoV-2 nucleocapsid mutations on the performance of the Panbio™ and BinaxNOW™ lateral flow rapid antigen tests and a prototype high-throughput immunoassay that utilizes Panbio antibodies. Variant detection was also evaluated by immunoblot and BIAcore™ assay. A panel of 23 recombinant nucleocapsid antigens (rAgs) were produced that included mutations found in circulating SARS-CoV-2 variants, including variants of concern. All mutant rAgs were detected by all assays, at a sensitivity equivalent to wild-type control (Wuhan strain). Thus, using a rAg approach, we found that the SARS-CoV-2 nucleocapsid mutations examined do not directly impact antigen detection or antigen assay performance.